(untitled) (Journal of the Management Sciences, 2025)
This study examined the effect of carbon emissions (Scopes 1, 2, and 3) and sustainability financial reporting on the firm value of selected listed firms in Nigeria. It assessed whether emission intensities and recognized sustainability frameworks significantly influence market valuation. Data were collected from nine listed Nigerian firms across key sectors for the period 2012–2023. Variables included emissions per revenue, sustainability reporting, firm size, leverage, and profitability. Descriptive and diagnostic tests were conducted, and model selection was guided by robustness checks. Hypotheses were tested using random effects panel regression with robust standard errors. Findings showed that Scope 2 and Scope 3 emissions had significant positive effects on firm value, with Scope 2 being the strongest predictor. Scope 1 emissions and sustainability reporting were not significant. Firm size and profitability had moderate positive impacts, while leverage showed weak effects. Diagnostic results confirmed model robustness. The findings suggest investors value indirect emissions disclosures (Scopes 2 and 3) more, especially when linked to operational efficiency, whereas inconsistent reporting limits the impact of Scope 1 and sustainability disclosures.